Surface electromyographic amplitude normalization methods: a review - Andreia S. P. Sousa (2012)
The electromyogram is the summation of the motor unit action potentials occurringduring contraction measured at a given electrode location. The voltage potential of thesurface electromyographic signal detected by electrodes strongly depends on severalfactors, varying between individuals and also over time within an individual. Thus, theamplitude of the EMG signal itself is not useful in group comparisons, or to follow eventsover a long period of time. The fact that the recorded electromyographic amplitude isnever absolute is mainly because impedance varies between the active muscle fibers andelectrodes and its value is unknown. The EMG signal is highly variable and is dependentupon many factors. Thus, the amplitude of the temporally processed electromyographycan only be used to assess short-term changes in the activity of a single muscle from thesame individual when the electrode setup has not been altered. To allow comparison ofactivity between different muscles, across time, and between individuals, the EMG signalshould be normalized, i.e. expressed in relation to a reference value obtained duringstandardized and reproducible conditions. Notwithstanding the importance of electromyographic amplitude normalization,studies on functional activities, such as gait, do not seem to show a uniformmethodology. Taking this into account, the main purpose of this chapter is to review anddiscuss different normalization procedures to relate the most appropriate method forspecific situations, based on how the normalization method might influence datainterpretation. In addition, this review supports the development of proper normalizationprocedures for biomechanical studies of functional activities like human gait.